The Influence of Rebozo Technique on the Duration of Active Phase of Stage I Labor in Primigravida Mothers at the Work Area of Pagelaran Primary Health Center - Raden Maria Veronika Widiatrilupi (Babali Health, 2023)
Introduction: Labor is a physiological process that involves the expulsion of the fetus, placenta, and membranes from the uterus through the birth canal. The active phase of Stage I labor is the most exhausting period for mothers, especially primigravida mothers. The use of the Rebozo technique is believed to assist the labor process. The function of the Rebozo technique is to provide a wider pelvic space for the mother, making it easier for the baby to descend into the pelvis and speeding up the labor process. The objective of this study was to determine the influence of the Rebozo technique on the labor process. Methode: This study employed a pre-experimental research design with a satisfic group comparison design approach. The study population consisted of primigravida mothers who received prenatal treatment at the work area of Pagelaran Primary Health Center, with total of 52 individuals. The sample consisted of 32 individuals who met the inclusion and exclusion criteria and were divided into two groups. Group 1: mothers who received the Rebozo technique, and Group II: mothers who did not receive the Rebozo technique. The measurement used in this study was the duration of Stage I labor. Result:  The data analysis employed the Chi-Square hypothesis test using SPSS software. The data from Group I indicated that the duration of labor was less than 6 hours for 14 respondents and more than 6 hours for 2 respondents. In Group II, 8 respondents without Rebozo technique had a labor duration of less than 6 hours, and 8 respondents had a labor duration of more than 6 hours. The hypothesis test yielded a p-value of 0.022 < 0.05, Conclusion: There are indicating an influence of the Rebozo technique on the duration of labor.